Español (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
This article recovers some results, from a gender perspective, obtained from a research carried out among women and men who participated in the sugar agroindustry in the province of Tucumán during the 50s and 60s. The aim is to make women visible from a different point of view than the one provided by the traditional historiography but also highlight the female and child workforce that were implemented by the capitalist, patriarchal sugar system of production by underestimating their labor participation. Therefore, build a new concept to incorporate women as active subjects in history instead of complementary workers plunging them into the lowest social strata that ended up forging a generational chain of poverty. KEY WORDS: Capitalism- Patriarchy-women-work-family